Virus. Poetics of Transgression (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
The article explores, based on Nietzsche's idea of "new infinity", the properties of contemporary space and time in aesthetic discourses. Likewise, it addresses the poetics of the virus as an infection and the strategies that correspond to it.
Keywords: virus; poetics; contemporary aesthetic; postpresnt